دراسة كمية المخلفات المعاشية المجمعة في مدينة اللاذقية وحاجتها من الحاويات و التوزيع المكاني لها باستخدام نظم المعلومات الجغرافية (GIS) - وزان, أحمد (Latakia University Journal -Engineering Sciences Series, 2016)
يعد التخلص من النفايات الصلبة من أهم القضايا البيئية المعاصرة , فنتيجة للزيادة السكانية و ما ارتبط بها من تغيير في أنماط و أساليب المعيشة و زيادة الاستهلاك , الامر الذي أدى الى زيادة كمية النفايات المنتجة و نوعيتها خاصة في المدن , حيث قدرت كمية النفايات الصلبة المنتجة يوميا في مدينة اللاذقية 840 طنا و بالتالي أصبح هناك حاجة ملحة لاتباع أساليب تقنية في إدارة النفايات الصلبة بكل مراحلها للحفاظ على صحة الإنسان و حماية البيئة من التلوث . تتلخص هذه الدراسة إلى تقدير كمية و خصائص النفايات الصلبة و الأساليب المتبعة في جمعها و تحليل التوزيع المكاني الحالي لحاويات جمع النفايات في مناطق مدينة اللاذقية , و التخطيط الأفضل لها بما يتناسب مع عدد السكان و كمية النفايات المنتجة باستخدام تقنية نظم المعلومات الجغرافية . و لإنجاز ذلك قمنا بمسح ميداني شامل لحاويات جمع النفايات في منطقة الدراسة حيث تم رصد مواقعها و التعرف على خصائصها , و اعتمدنا على المنهج الإحصائي التحليلي في توظيف البيانات التي تم الحصول عليها , و بالاستعانة بالخريطة الدليلية لمدينة اللاذقية و من خلال برنامج (ARC GIS 9.3) تم إدخال البيانات و معالجتها و الربط بينها و تحليلها باستخدام أدوات التحليل الملحقة بالبرنامج و الخروج بالخرائط و الأشكال المختلفة التي تخدم الدراسة . و توصلت الدراسة الى أن عدد الحاويات الحالية يعد غير كافيا عند تفريغها يوميا ,وكما أن توزيعها المكاني لا يتناسب مع كمية النفايات المنتجة في مناطق المدينة The disposal of solid waste is one of the most important contemporary environmental issues. Increasing population and what has been associated with the change in the patterns and lifestyles and increased consumption led to increasing the amount of produced waste and its quality, especially in cities; the estimated amount of solid waste produced daily in the city of Latakia was 840 tons. Thus, there is an urgent need to follow the techniques in the management of solid waste in all stages to maintain human health and protect the environment from pollution. This study as a whole aims to estimate the amount and characteristics of solid waste, the methods used to collect and analyze the spatial distribution of the current waste collection containers in areas of the city of Latakia, better planning commensurate with its population and the amount of waste produced using GIS technology. To accomplish this, we have a comprehensive field survey to collect the waste containers in the study area where they were monitoring their locations and identifying characteristics; we relied on statistical analytical approach in the recruitment of data that have been obtained, and used the map to the city of Latakia Tags. And, through the program (ARC GIS 9.3) the data has been entered and processed, linked and analyzed using analysis tools attached to the program, exit maps and various forms that serve the study. The study concludes that the current number of containers is not enough when discharged per day, and that the spatial distribution is not commensurate with the amount of waste produced in areas of the city .